Concentration of lead and zinc in greenhouse cucumbers of Hamadan province in 2012 - Z BigMohammadi; K Shayesteh; M Cheraghi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
Heavy metal pollution of agricultural soils is a major environmental problem that can affect plant production, food safety and human health. Soil contamination with heavy metals occurs as a result of human activities. Heavy metals can easily accumulate in edible tissues of leafy vegetables, fruits and seeds. Few studies have been conducted on heavy metals concentration in soil and greenhouse crops. Therefore, this study aimed to determine the concentrations of lead (Pb) and zinc (Zn) in greenhouse cucumbers produced in Hamadan province. The concentrations of heavy metals were measured using atomic emission method. Results showed that the mean concentrations of Pb and Zn in cucumber samples were 0.33 and 3.14 mg/kg, respectively. Also the results of the statistical analysis revealed a negative correlation between the measured concentrations. Moreover, the concentration of Zn in the samples obtained from Hamadan greenhouses and lead concentration in Tuyserkan, Famenin, as well as Malayer samples were above the recommended limits. Daily intake amounts of Pb and Zn from vegetables consumption for three age categories (children, adolescents, and adults) were calculated. In conclusion, daily intake of Pb and Zn were determined below the recommended limits.